What are the challenges of medical education development offices and centers in universities of medical sciences? - Parvin Rezaei Gazki; Mahla Salajegheh (Zanjan University of Medical Sciences and Health Services, 2024)
The demands on educational managers in medical universities are growing as a result of organizational transformations in healthcare, the increasing complexity of healthcare services, and evolving concepts in medical education, such as new teaching methods, assessment, and learning approaches (1). These demands aim to enhance the quality of medical education and provide better healthcare services to the community. To meet these needs, various strategies are proposed. It is essential to have education development centers (EDCs) and Educational Development Offices (EDOs) that are responsible for guiding and improving the quality of educational activities in universities (2). Studies have shown that the presence of EDCs has led to the improvement of educational quality in medical science universities (3). To manage the quality of educational development activities across all educational institutions within universities, EDOs operate as the executive body of the EDC within medical schools and educational centers. These offices have defined some responsibilities at the conceptual, executive, and supervisory levels to guide the development of educational quality in faculties and teaching hospitals. However, can these offices cope well with these huge tasks? Educational Development Offices face various challenges that reduce their effectiveness in fulfilling these responsibilities. The major known challenges that EDCs and EDOs confront in performing their roles for the development of medical education within medical universities include inadequate familiarity of planners, policymakers, and faculty members with education as a specialized field; inadequacy of educational strategies and programs at universities; issues related to student evaluation of professors and communication of the evaluation results to faculty members; attention to differences in teaching experience and background among faculty members in conducting faculty development programs; supervision of implemented teaching methods by faculty members; and the adoption of various electronic teaching methods. Among the other challenges, one can mention multiple organizational roles of faculty members and the justification of the importance and responsibilities of EDOs by college/hospital administrators and even some EDCs (3-5). The results of conducted studies demonstrated that challenges arising from a lack of scientific awareness or organizational importance are fundamentally significant. These challenges include limited familiarity of educational planners and policymakers with the science of education, as well as an absence of profound understanding by college/hospital administrators and even some EDOs and EDCs of the importance and responsibilities of educational development offices. University faculty members face serious challenges in managing these offices due to their multiple organizational roles and responsibilities within the university. For instance, clinical faculty members should manage hospital-based educational development offices, which, in addition to their educational, clinical, and research roles, present some difficulties. Performing this task becomes more challenging when hospital administrators fundamentally do not believe in the necessity of these offices for improving the quality of the hospital. Considering the increasing complexity and multidimensionality of educational processes in medical universities, and based on existing evidence, it is doubly important to support the readiness of collaborating faculty members in educational development offices to fulfill leadership roles and embrace managerial responsibilities, while also creating motivation to engage in practical and complex issues related to enhancing learning quality. Emphasizing formal and informal training programs within organizations and raising awareness among influential individuals in the education field can be useful in addressing these challenges. Enhancing management and leadership skills through relevant empowerment courses will lead to a change in the perception of leadership roles; gaining awareness of the organization's impact on educational leaders' performance, organizational mission, and commitment to fulfilling them; self-awareness of strengths and weaknesses; increased motivation and self-confidence in assuming leadership responsibilities; increased knowledge of leadership concepts, principles, and strategies; changing one's leadership style; and embracing new leadership roles and responsibilities (6). Focusing on the quality of medical education is at the core of the responsibilities of educational institutions, and to achieve this, it is required to establish and strengthen organizational mechanisms, including the creation and enhancement of educational development offices in faculties and hospitals. Paying attention to the challenges faced by these organizations and striving to address them will significantly enhance the quality of education. To overcome these challenges, the engagement and commitment of all beneficiaries within universities, including administrators and faculty members, are required.